Antioxidant activities, total phenolic content and colour parameters in the aqueous extracts of avocado, banana and papaya leaves - Nirvesha Nair Vijaya Kumar Gopalan; Tan, Seok Tyug (Penerbit Universiti Kebangsaan Malaysia, 2021)
Literature has consistently reported that horticultural wastes including leaves, skin, stones and seeds contain substantial amounts of bioactive compounds. Therefore, this study aims to evaluate antioxidant activity, Total Phenolic Content (TPC) and colour parameters in avocado, banana, and papaya leaves. Antioxidant activity of the leaves was determined using Trolox Equivalent Antioxidant Capacity (TEAC) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assays, TPC was evaluated using Folin-Ciocalteu assay whereas the colour parameters were analysed with a colour picker software. Data analysis was carried out using SPSS version 25.0 of triplicate determinations. Mean differences among the fruit leaves extracts were determined using One-way ANOVA, while the correlations between the studied components were by the Pearson’s Correlation Coefficient test. The TEAC values were in the range of 332.30 ± 18.04 µg Trolox/g D.W. (avocado leaves) to 12217.71 ± 18.04 µg Trolox/g D.W. (banana leaves) while the DPPH radical scavenging activity was from 10.07 ± 3.89% (banana leaves) to 86.70 ± 0.26 % (avocado leaves). Besides, TPC was from 871.33 ± 38.35 µg GAE/g D.W. (papaya leaves) to 1199.08 ± 6.00 µg GAE/g D.W. (avocado leaves). The hue values were from 19º in avocado leaves extract to 37º in banana leaves extract. Results from Pearson’s Correlation Coefficient test revealed that there were no significant correlations between the studied assays. Avocado leaves had the highest DPPH radical scavenging activity and TPC among the three extracts. Findings derived from the present study could be exploited in nutraceuticals formulation.